2011
DOI: 10.3109/07420528.2011.569043
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Dosing-Time Dependencies in Irinotecan-Induced Circadian Disruption

Abstract: Circadian disruption accelerates malignant growth; thus, it should be avoided in anticancer therapy. The circadian disruptive effects of irinotecan, a topoisomerase I inhibitor, was investigated according to dosing time and sex. In previous work, irinotecan achieved best tolerability following dosing at zeitgeber time (ZT) 11 in male and ZT15 in female mice, whereas worst toxicity corresponded to treatment at ZT23 and ZT3 in male and female mice, respectively. Here, irinotecan (50 mg/kg intravenous [i.v.]) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…In contrast, CTS re-enforcement with meal timing, a potent synchronizer of peripheral clocks, nearly halves experimental tumor growth (Filipski et al, 2005; Li et al, 2010; Wu et al, 2004). Anticancer drugs can also disrupt both circadian activity and temperature patterns, as well as molecular clocks, as a function of dose and circadian timing in mice (Ahowesso et al, 2011; Lévi et al, 2010; Li et al, 2002; Ohdo et al, 2001). Thus, the temperature circadian rhythm appears both as a biomarker of CTS function and as an endogenous synchronizer of peripheral clocks.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, CTS re-enforcement with meal timing, a potent synchronizer of peripheral clocks, nearly halves experimental tumor growth (Filipski et al, 2005; Li et al, 2010; Wu et al, 2004). Anticancer drugs can also disrupt both circadian activity and temperature patterns, as well as molecular clocks, as a function of dose and circadian timing in mice (Ahowesso et al, 2011; Lévi et al, 2010; Li et al, 2002; Ohdo et al, 2001). Thus, the temperature circadian rhythm appears both as a biomarker of CTS function and as an endogenous synchronizer of peripheral clocks.…”
Section: Introductionmentioning
confidence: 99%
“…Irinotecan efficacy and toxicity displayed circadian rhythms in groups of mice and patients (2,17). Several genes and proteins involved in irinotecan PK and/or PD display circadian rhythms in mouse liver and/or intestine, including the drug target Top1 (18), the bioactivation enzymes Ces1 and Ces2 (19), the detoxification enzyme Ugt1a1 (19), and the efflux transporters Abcb1a, Abcb1b, and Abcc2 (17,18,(20)(21)(22). Studies in 8 mouse categories, based on differences in sex and genetic background, revealed large differences in irinotecan chronopharmacology.…”
Section: Introductionmentioning
confidence: 99%
“…Two separate clinical trials uncovered that the optimal timing of a multidrug chronomodulated chemotherapy protocol could lag 6 h behind in women as compared to men with this same cancer type [63,64]. Such differences in circadian amplitudes, and time lag between males and females were similar in cancer patients and in mouse models [65,66]. The sex-related differences in circadian timing system that were discovered here could explain why the same multidrug cancer chronotherapy protocol improved response rate, progression-free survival and overall survival in men, but not in women with metastatic colorectal cancer, independently of all other prognostic factors within a meta-analysis of three randomized international clinical trials involving 842 patients [28].…”
Section: Sex and Age As Important Determinants Of Circadian Coordinatmentioning
confidence: 86%